Using innovation and entrepreneurship for creating edge in service firms: A review research of tourism and hospitality industry - Gagan Deep Sharma; Babak Taheri; Dariusz Cichoń; Jaya Singh Parihar; Aeshna Kharbanda (Journal of Innovation & Knowledge (JIK), 2024)
This paper aims to inform policy and research in the domain of tourism and hospitality on the role of innovation and entrepreneurship. The paper applies the review research methodology to collate, comprehend, and synthesise 139 papers selected through a standard procedure. Our findings show that innovation drives growth and value in new tourism and hospitality firms. The study examines external factors, particularly government policies, influencing industry stakeholders' entrepreneurial orientation and the macroeconomic environment affecting entrepreneurial activities. It also highlights the importance of social entrepreneurship in industry innovation and sustainability. This article emphasises the importance of innovation and entrepreneurship in tourism and hospitality growth, value creation, and social and environmental issues.
Keywords: D83; L26; L83; O31; Q01; Q56; 650; innovation; entrepreneurship; digital transformation; knowledge sharing; tourism and hospitality industry